TIC-320687387 B: a long-period eclipsing M-dwarf close to the hydrogen burning limit. Issue 2 (29th March 2022) - Gill, Samuel; Ulmer-Moll, Solène; Wheatley, Peter J; Bayliss, Daniel; Burleigh, Matthew R; Acton, Jack S; Casewell, Sarah L; Watson, Christopher A; Lendl, Monika; Worters, Hannah L; Sefako, Ramotholo R; Anderson, David R; et al.
ABSTRACT: We are using precise radial velocities from CORALIE together with precision photometry from the Next Generation Transit Survey (NGTS) to follow-up stars with single-transit events detected with the Transiting Exoplanet Survey Satellite ( TESS ). As part of this survey, we identified a single transit on the star TIC-320687387, a bright ( T = 11.6) G-dwarf observed by TESS in Sectors 13 and 27. From subsequent monitoring of TIC-320687387 with CORALIE, NGTS, and Lesedi we determined that the companion, TIC-320687387 B, is a very low-mass star with a mass of 96.2 ± _2.0^1.9 M J and radius of 1.14 ± _0.02^0.02 R J placing it close to the hydrogen burning limit (∼80 M J ). TIC-320687387 B is tidally decoupled and has an eccentric orbit, with a period of 29.77381 d and an eccentricity of 0.366 ± 0.003. Eclipsing systems such as TIC-320687387 AB allow us to test stellar evolution models for low-mass stars, which in turn are needed to calculate accurate masses and radii for exoplanets orbiting single low-mass stars. The sizeable orbital period of TIC-320687387 B makes it particularly valuable as its evolution can be assumed to be free from perturbations caused by tidal interactions with its G-type host star.